Artiguism, restoration and strategic uses of the past - Moreno Barreneche, Sebastián (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
This article studies, from a semiotic-discursive perspective, the identity-building process of the Uruguayan political party Cabildo Abierto, founded to compete in the 2019 national elections. Given its semiotic approach, the article studies the party's identity proposal through the use made of certain pre-existing resources, discourses, and social imaginaries. From a constructivist premise, a theoretical framework is first presented, which will allow to study the discursive dimension of political activity. Particular attention is given to the constitution of the collectives which, as argued, are at the basis of the functioning of this discursive field. Subsequently, a set of materials presented by Cabildo Abierto and some of its representatives are analyzed, in order to study how this collective identity comes to life, from a collection of pre-existing discursive resources in the Uruguayan public sphere.